1992
DOI: 10.1007/bf00582160
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid-induced osteoporosis in the lumbar spine, forearm, and mandible of nephrotic patients: A double-blind study on the high-dose, long-term effects of prednisone versus deflazacort

Abstract: The long-term effects of high dose steroid treatment with either prednisone (PDN) or deflazacort (DFZ) were examined on various parts of the skeleton in 29 patients with nephrotic syndrome. All had normal skeleton at the start of the steroid treatment. At the beginning, PDN was given as 80 mg/day and tapered down to 20 mg/day for 1 year and DFZ was given in an equipotent dosage. Twenty-three patients completed 6 months of treatment, and 18 patients completed 12 months of treatment. Beside laboratory parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(33 citation statements)
references
References 20 publications
0
33
0
Order By: Relevance
“…Olgaard et al [5] found a similar efficacy of high doses of both drugs in terms of reduction of proteinuria. Piccoli et al [15], using the same equipotent ratio as in the present study, found a greater efficacy of DFZ in a short-term (2 × 5 weeks) crossover study.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Olgaard et al [5] found a similar efficacy of high doses of both drugs in terms of reduction of proteinuria. Piccoli et al [15], using the same equipotent ratio as in the present study, found a greater efficacy of DFZ in a short-term (2 × 5 weeks) crossover study.…”
Section: Discussionmentioning
confidence: 92%
“…Deflazacort (DFZ), a synthetic heterocyclic oxazoline glucocorticoid, was shown to be as effective as prednisone (PDN) in diseases such as rheumatoid arthritis [1][2][3], juvenile chronic arthritis [4], adult nephrotic syndrome [5], perhaps asthma [6], and also in kidney [7] and heart [8] transplantation, with a lower overall incidence of adverse effects, as recently reviewed by Markham and Bryson [9]. Children with the nephrotic syndrome seemed to develop fewer side effects of steroid therapy under DFZ in an uncontrolled study [10], and it appeared important to go further.…”
Section: Introductionmentioning
confidence: 99%
“…This seems particularly pertinent to corticosteroid-dependent NS, since a proportion of these patients may eventually develop renal insufficiency and ESRD [19,30], with consequent renal osteodystrophy [20], and eventually may require renal transplantation with further exposure to corticosteroid therapy and risk of fractures [51]. Reports on the use of growth hormone [52], bone-sparing corticosteroids like deflazacort [53], calcitonin, and vitamin D [54], and more recently bisphosphonates [55] are encouraging. However, long-term longitudinal studies evaluating peak bone mass and possibly bone histomorphometry in patients with prolonged NS are needed.…”
Section: Discussionmentioning
confidence: 97%
“…A similar rebound increase in boneforming activity also occurs following the discontinuation of chronic glucocorticoid therapy [73]. Deflazacort, a recently developed oxazoline derivative of prednisolone, has been reported to have reduced damaging effects on bone mass relative to its antiinflammatory actions [74]. Short-term studies have shown a stimulatory effect of nandrolone deconate (Table 3) on bone density in postmenopausal women on glucocorticoids [75].…”
Section: Other Potential Indications For Measurements Of Bone Mass: Amentioning
confidence: 99%